Education of Adolescents about Anemia and Reproductive Health as A Stunting Prevention Effort - Reviani, Nia; Amira Oktaria, Sarah; Syefi Febriyanti, Monica; Rahayu Samaria, Adinda; Yulanda, Buca; Jutan Sanjaya, Stevanus; Harlim, Ago (International Journal Of Community Service, 2025)
Teenagers are an asset and the next generation of the nation, where the future of the nation and state for the future is in their hands. For this reason, it is crucial and inevitable to pay attention to the condition of teenagers today, including their health, specifically regarding reproductive health. Anemia and reproductive health are two things that cannot be separated when talking about adolescent health to prepare them to become a generation that will also have children. It is hoped that the long chain of the stunting phenomenon can be slowly reduced and even broken by preparing the current generation to become a generation that is ready and healthy both physically and physically. Community service activities with the theme of youth education about anemia and reproductive health in Rancakalong Village and Pamekaran Village involved 53 participants consisting of young women with sociodemographic characteristics of early teens and late teens, with junior and senior high school education. The activity results showed an increase in young women's knowledge about anemia and reproductive health, where based on the post-test results, an average score of 88.4 ± 5.6 was obtained from the pre-test results of 59.5 ± 12.6. Thus, it can be concluded that educational activities are significantly useful in increasing young women's knowledge in Rancakalong and Pamekaran villages about anemia and reproductive health.